Performance of bat-derived macrophages at different temperatures - Nemcova, Monika; Seidlova, Veronika; Zukal, Jan; Dundarova, Heliana; Zukalova, Katerina; Pikula, Jiri (Frontiers in veterinary science, 2022)
Heterothermy, as a temperature-dependent physiological continuum, may affect host-pathogen interactions through modulation of immune responses. Here, we evaluated proliferation and functional performance of a macrophage cell line established from the greater mouse-eared (Myotis myotis) bat at 8, 17.5, and 37°C to simulate body temperatures during hibernation, daily torpor and euthermia. Macrophages were also frozen to -20°C and then examined for their ability to proliferate in the immediate post-thaw period. We show that bat macrophages can proliferate at lower temperatures, though their growth rate is significantly slower than at 37°C. The cells differed in their shape, size and ability to attach to the plate surface at both lower temperatures, being spheroidal and free in suspension at 8°C and epithelial-like, spindle-shaped and/or spheroidal at 17.5°C. While phagocytosis at temperatures of 8 and 17.5°C amounted to 85.8 and 83.1% of the activity observed at 37°C, respectively, full phagocytic activity was restored within minutes of translocation into a higher temperature. Bat-derived macrophages were also able to withstand temperatures of -20°C in a cryoprotectant-free cultivation medium and, in the immediate post-thaw period, became viable and were able to proliferate. Our in vitro data enhance understanding of macrophage biology.
Keywords: macrophage biology; daily torpor; temperature-dependent proliferation; phagocytic activity; Chiroptera (bats); in vitro model; hibernation